2020
DOI: 10.1074/jbc.ra120.013976
|View full text |Cite
|
Sign up to set email alerts
|

The GTPase-activating protein p120RasGAP has an evolutionarily conserved “FLVR-unique” SH2 domain

Abstract: The Src homology 2 (SH2) domain has a highly conserved architecture that recognizes linear phosphotyrosine motifs and is present in a wide range of signaling pathways across different evolutionary taxa. A hallmark of SH2 domains is the arginine residue in the conserved “FLVR” motif that forms a direct salt bridge with bound phosphotyrosine. Here, we solve the X-ray crystal structures of the C-terminal SH2 domain of p120RasGAP (RASA1) in its apo and peptide-bound form. We find that the arginine residue in the F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 86 publications
(124 reference statements)
2
17
0
Order By: Relevance
“…One of the first SH2 proteins to be identified was p120RasGAP (RasGAP, RASA1) (69-71), and for 30 years it was thought to contain two canonical SH2 domains (termed the N-and C-terminals SH2s) (72)(73)(74). We investigated p120RasGAP, and our crystal structure and mutagenic analysis of the N-terminal SH2 domain showed this to be correct for the N-terminal domain (75), however, we found that the C-terminal SH2 domain assumes a completely unexpected mode of pTyr recognition (76). Instead of contacting the conserved phosphotyrosine as observed in every other SH2-pTyr interaction, the FLVR arginine at residue position 377 makes a salt bridge to an aspartic acid at position 380.…”
Section: A Diversity Of Flvrmentioning
confidence: 94%
See 1 more Smart Citation
“…One of the first SH2 proteins to be identified was p120RasGAP (RasGAP, RASA1) (69-71), and for 30 years it was thought to contain two canonical SH2 domains (termed the N-and C-terminals SH2s) (72)(73)(74). We investigated p120RasGAP, and our crystal structure and mutagenic analysis of the N-terminal SH2 domain showed this to be correct for the N-terminal domain (75), however, we found that the C-terminal SH2 domain assumes a completely unexpected mode of pTyr recognition (76). Instead of contacting the conserved phosphotyrosine as observed in every other SH2-pTyr interaction, the FLVR arginine at residue position 377 makes a salt bridge to an aspartic acid at position 380.…”
Section: A Diversity Of Flvrmentioning
confidence: 94%
“…This salt bridge is unprecedented in SH2 domains and requires that pTyr binding is achieved by a unique mechanism that uses multi-dentate recognition by basic residues at βD4 and βD6, and by residues in the BC loop ( Figure 2J). The reason for this unusual binding mode is currently unknown, but it is highly conserved over evolution, only diverging in extremely ancient examples of p120RasGAP (76). Despite being one of the first identified and best studied SH2 domain proteins, the C-terminal SH2 domain of p120RasGAP has revealed another mechanism by which SH2 domains can achieve their purpose as protein interaction domains.…”
Section: A Diversity Of Flvrmentioning
confidence: 99%
“…Crystal structures of different pY-peptides bound to the nSH2 and cSH2 domains of RASA1 show a preference of the two SH2 domains for the pYxxP motif (where x represents any natural amino acid) with a proline residue at the +3 position C-terminal to pY (Figure S3). ,, In EGFR, two sites, pY992 (pYLIP) and pY1101 (pYQDP), match this motif. The RASA1-binding site also raises questions such as how SHP2 influences RASA1’s regulation of EGFR-dependent Ras signaling, and how RASA1 recognizes EGFR’s pY site in recruitment.…”
Section: Introductionmentioning
confidence: 99%
“…It is unclear however which redundancies exist during NRP1-directed and NRP2-directed α5β1 integrin traffic, and which endocytic complexes participate. p120RasGAP (alias: RASA1) is a ubiquitously expressed endosomal GTPase-activating protein (GAP) that contains canonical phospho-Tyrosine (pTyr)-interacting SH2 domains [14], [15]. As an important negative regulator of the Ras signalling cascade, p120RasGAP global knockout (KO) mice exhibit major vascular defects that result in embryonic lethality [16].…”
Section: Introductionmentioning
confidence: 99%